Integrasi Pelatihan Pojok Seni dan Aplikasi Digital dalam Meningkatkan Kualitas Masyarakat Gunung Anyar Tambak Kota Surabaya - Nathania Candra Fadhillah; Salsabila Ahmad (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The art corner and digital application training in Gunung Anyar Tambak, Surabaya, aims to improve the quality of life of the community through creativity and skills development. This study analyzes the impact of the training program on community participation, social welfare improvement, and contribution to creativity development. The research method used is a qualitative approach by conducting interviews to identify community satisfaction during training, and then conducting interviews with dance training students in depth to explore the potential of students after attending dance training. The results showed that the program succeeded in increasing community interest and participation in arts activities, and had a positive impact on social and economic aspects. This training activity has an impact on increasing the motivation and ability of the community in the use of technology in the current era. Through a training program that involves the active participation of the community, this research analyzes the impact of the program on increasing the sense of belonging to local culture, creative economic development, and the formation of stronger social networks.